2011
DOI: 10.1021/jf200226p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Treatment on Mineral Nutrition, Bulb Size, and Antioxidant Properties of Garlic (Allium sativum L.)

Abstract: Foliar selenium (Se) treatment of garlic at concentrations of 10, 50, and 100 μg of Se/mL was carried out in open field conditions in 2008 and 2009 in Estonia. Bulb weight and yield structure, content of total Se, S, N, P, K, Ca, and Mg, ascorbic acid content (AAC), pungency, total phenolics, and total antioxidant capacity (TAC) were determined. The highest level of Se decreased total S, K, and Ca in both years; no negative impact on bulb weight was observed. In 2009 Se10 treatment had significantly more bulbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 29 publications
(49 reference statements)
3
38
1
Order By: Relevance
“…Hacıseferoğulları et al [24] and Akinwande and Olatunde [26] have also reported significant amounts of K in garlic bulbs, while Mg, Na and Ca were also detected in considerable amounts. In addition, fertilizer application rates and soil properties may have a significant effect on the mineral composition of garlic bulbs, as previously supported by Diriba-Shiferaw et al [15] Põldma et al [27] have also reported that although Se fertilization is recommended for larger bulbs and better antioxidant activity of garlic, high Se application rates can result in the replacement of S by Se in plant metabolism and consequently the decrease in the content of essential macronutrients such as P, K and Ca.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Hacıseferoğulları et al [24] and Akinwande and Olatunde [26] have also reported significant amounts of K in garlic bulbs, while Mg, Na and Ca were also detected in considerable amounts. In addition, fertilizer application rates and soil properties may have a significant effect on the mineral composition of garlic bulbs, as previously supported by Diriba-Shiferaw et al [15] Põldma et al [27] have also reported that although Se fertilization is recommended for larger bulbs and better antioxidant activity of garlic, high Se application rates can result in the replacement of S by Se in plant metabolism and consequently the decrease in the content of essential macronutrients such as P, K and Ca.…”
Section: Resultsmentioning
confidence: 63%
“…Vargas et al [29] have reported similar results for Argentinian garlics, where they observed significant differences in the pyruvic acid content not only between different cultivars from the same area but also between the same cultivar grown in different areas. According to Põldma et al [27] sulfur fertilizer rates may have a significant effect on pyruvic acid content and consequently on bulb pungency.…”
Section: Resultsmentioning
confidence: 99%
“…Poldma et al (2011) showed a significant negative correlation between Se and S concentration in Se treated garlic. Similarly, Poldma et al (2013) reported significant reducing S content in onion bulbs as affected by different Se treatments. The contradiction between different studies can be related to either foliar spray of Se that impede uptake competition between Se and S, or associated with applied appropriate doses of Se in some studies, which prevented S assimilation disorder.…”
Section: Mineral Elements Concentrationmentioning
confidence: 86%
“…S can be replaced by Se in different organic compounds, especially in sulfuric amino acids, including methionine and cysteine (Terry et al, 2000). Poldma et al (2011) showed a significant negative correlation between Se and S concentration in Se treated garlic. Similarly, Poldma et al (2013) reported significant reducing S content in onion bulbs as affected by different Se treatments.…”
Section: Mineral Elements Concentrationmentioning
confidence: 95%
“…In the literature, there are many scientific reports of ICP-MS analysis for the determination of mineral concentration in food matrices including garlic [5,6,7,8,9,10,11]. Furthermore, nowadays there is great attention paid to the discrimination of protected foodstuffs [12,13,14].…”
Section: Introductionmentioning
confidence: 99%